PENGARUH PEMBELAJARAN PENDIDIKAN AGAMA KATOLIK TERHADAP PERKEMBANGAN IMAN DAN PERUBAHAN PERILAKU SISWA SEKOLAH MENENGAH PERTAMA KATOLIK DI KOTA MADIUN - Dicky Melyawanto; Ola Rongan Wilhelmus (Lembaga Penelitian STKIP Widya Yuwana, 2019)
The task of organizing education is primarily the responsibility of parents and assisted by the community as long as it is needed. The task of organizing education is also the responsibility of the Church. The Church takes part in the world of education, among others, through Catholic religious education in Catholic schools. The learning process of Catholic Religious Education is intended to improve the faith of Catholic youth. The research was conducted by using qualitative research method. Qualitative research method is a form of research designed to examine attitudes, views, feelings, and behavior of individuals or groups of people or social issues being investigated. This study aims to analyze the extent to which Catholic Religious Education affects the development of faith and behavioral change of the Catholic Junior High School students in Madiun. The results of the research indicated that 7 (58%) of respondents stated that junior high school students were students between 13-15 years old. There were 12 (100%) respondents said that Catholic Religious Education taught in the School was able to help the junior high school students to have more knowledge about Jesus and his preaching. As many as 6 (50%) of respondents stated that Catholic Religious Education is very helpful to get know more about themselves personally. There were 8 (67%) of respondents stated that the teaching of Catholic Religion made their faith progressively improved. Broadly speaking, all respondents experienced that Catholic Religious teaching has made their Catholic faith being developed so far. It made the respondents more diligent and actively involved in throughout Catholic Church activities and any social affairs.